Genome‐wide binding analysis reveals that ANAC060 directly represses sugar‐induced transcription of ABI5 in Arabidopsis. (18th May 2020) - Yu, Bo; Wang, Yuejun; Zhou, Hua; Li, Ping; Liu, Chunmei; Chen, Sunlu; Peng, Yu; Zhang, Yijing; Teng, Sheng
SUMMARY: The sugar status of a plant acts as a signal affecting growth and development. The phenomenon by which high levels of sugars inhibit seedling establishment has been widely used to gain insight into sugar‐signaling pathways. Natural allelic variation has been identified at the ANAC060 locus. The Arabidopsis Columbia ecotype produces a short ANAC060 protein without a transmembrane domain that is constitutively located to the nucleus, causing sugar insensitivity when overexpressed. In this study, we generated a genome‐wide DNA‐binding map of ANAC060 via chromatin immunoprecipitation sequencing using transgenic lines that express a functional ANAC060–GFP fusion protein in an anac060 background. A total of 3282 genes associated with ANAC060‐binding sites were identified. These genes were enriched in biotic and abiotic stress responses, and the G‐box binding motif was highly enriched in ANAC060‐bound genomic regions. Expression microarray analysis resulted in the identification of 8350 genes whose activities were altered in the anac060 mutant and upon sugar treatment. Cluster analysis revealed that ANAC060 attenuates sugar‐regulated gene expression. Direct target genes of ANAC060 included equivalent numbers of genes that were upregulated or downregulated by ANAC060 . The various functions of these target genes indicate that ANAC060 has several functions. Our results demonstrate that ANAC060 directly binds to the promoter of ABI5 and represses the sugar‐induced transcription of ABI5 . Genetic data indicate that ABI5 is epistatic to ANAC060 in both sugar and abscisic acid responses. Significance Statement: Constitutive expression of an Arabidopsis Columbia ANAC060 allele suppresses the sugar–ABA signaling cascade which controls important processes in plants, such as photosynthesis and growth. In this study, we generated a genome‐wide DNA‐binding map of ANAC060, indicating that it directly binds to a G‐box motif. ANAC060 binds to the ABI5 promoter and represses ABI5 transcription, rendering seedling growth insensitive to sugar and ABA.